Jual Beli Ayam Sabung Perpektif Fikih Muamalah - Maulana, Ivanda Singgih; Trigiyatno, Ali (el hisbah Journal of Islamic Economic Law, 2023)
Cockfighting has become a legal culture in the mulsim community of Batang Regency, Central Java. Consumers who want to buy will usually first ask for the characteristics of the sabung chicken in question or the type of chicken that is being sought, then the seller will provide several choices of sabung chickens that are sold to be given to prospective buyers then if the buyer matches the sabung chicken there is a bargaining process until he gets the appropriate price then payment is made in cash to the seller. But this is contrary to the norms of sharia economic law. This research aims to analyze more deeply about the sale and purchase of sabung chicken from the point of view of muamalah fiqh. This research method includes empirical juridical research using a qualitative approach. Data collection techniques using interview techniques, observation and documentation. The analysis technique used is qualitative analysis of interactive models. The results of this study indicate that the sale and purchase of sambung chicken is prohibited because although the pillars of this sale and purchase are valid, the legal conditions for this sale and purchase are not fulfilled. This is due to the purpose of most people who buy sabung chicken to be used as a bet in cockfighting.